Strength and Durability of Sand Cement Brick Containing Recycled Concrete Aggregate (RCA) and Waste Fired Clayed Brick (FCB) As Partial Sand Replacement Materials - Khalid, F. S.; Saaidin, S. H.; Irwan, J. M.; Anak Guntor, N. A.; Siang, A.J.L.M (Journal of Structural Monitoring and Built Environment, 2023)
The use of burnt clayed brick (FCB) and recycled coarse aggregate (RCA) in cementitious materials aids in the reuse of clay brick waste from construction and demolition works. In fact, concrete manufacturing expanded in lockstep with the Malaysian economy’s expansion. The purpose of this study is to determine the strength and durability of sand cement brick containing recycled concrete aggregate (RCA) and waste fired clayed brick (FCB) as partial sand replacement materials. According to the findings, a brick containing 0% RCA and 2% FCB has the best compressive strength, while a brick containing 15% RCA and 6% FCB has the lowest water absorption when compared to other mix designs and is the best mix design for water absorption. Lastly, it is steadily applicable the RCA and FCB as second sources of natural coarse aggregate and can reduce waste of concrete aggregate and FCB.